Tetraciclinas: un modelo de resistencia antimicrobiana - Jara, María (Avances en Ciencias Veterinarias, 2007)
Tetracyclines are a group of broad-spectrum antibiotics whose general usefulness has been reducedTetracyclines are a group of broad-spectrum antibiotics whose general usefulness has been reduced with the onset of bacterial resistance. Tetracycline resistance is the most frequent bacterial antibiotic resistance found in nature and is mostly acquired by horizontal gene transfer. Nowadays, 39 acquired tetracycline determinants are known for bacteria. Nucleic acid-based detection systems offer rapid and sensitive methods to detect the presence of resistance genes and play a critical role in the elucidation of resistance mechanisms. Resistance to the antibiotic is conferred by 1 or more of the 39 currently described tet genes, which encode one of three mechanisms of resistance: use of an energy dependent efflux of tetracycline, altering the ribosome to prevent effective binding of the tetracycline, and producing tetracycline-inactivating enzymes. Efflux mechanisms appear to be more abundant among gram-negative microorganisms, while ribosomal protection mechanisms are more common among gram-positive organisms. Generally speaking, the rapid spread of tetracycline resistance among bacteria is due to the localization of tet genes on plasmids, transposons, and integrons. Molecular analysis of bacterial resistance has yielded a wealth of information during the last decade. With the aid of molecular amplification techniques, great progress has been made in our knowledge of the distribution and spread of resistance markers among the species.